PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK PERUSAHAAN DENGAN WOMEN DIRECTORS SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Naisya Nanda Pratiwi; Nur Cahyonowati (Diponegoro Journal of Accounting, 2025)
Taxation is a primary source of state revenue that plays a strategic role in supporting sustainable development, particularly in providing public facilities to enhance community welfare. However, the achievement of tax revenue targets in Indonesia still faces various challenges, one of which is due to tax avoidance practices by businesses. The level of tax avoidance by companies can be influenced by the implementation of corporate social responsibility, as socially responsible companies tend to prioritize social values for the welfare of the community and the surrounding environment. Using unbalanced panel data from 86 companies listed on the Indonesia Stock Exchange from 2021 to 2023 with 201 observations, this study aims to examine the effect of corporate social responsibility on corporate tax avoidance, with women directors as a moderating variable. This research also includes firm size, leverage, return on assets (ROA), institusional ownership, audit committee size, and dummy variable of the tax regulation harmonization law as control variables.A panel data regression analysis with the Random Effect Model (REM) estimator was employed to investigate the effect of corporate social responsibility in corporate tax avoidance with women directors as a moderating variable.The results show that corporate social responsibility has a significant negative effect on corporate tax avoidance. However, women directors do not significantly moderate the negative effect of corporate social responsibility on corporate tax avoidance. Therefore, it can be concluded that women directors serve as a homologizer moderator or a variable considered to have the potential to act as a moderating variable.